(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
New finds of remarkable coprolites (fossilized feces) are here reported from the famous Miocene marine sediments of the Chesapeake Group exposed along Calvert Cliffs (Maryland, U.S.A.). Although vertebrate coprolites have been described from these deposits, here we provide the first description of tiny invertebrate fecal pellets. Thus far, these fecal pellets have only been found in the upper Miocene (Tortonian) St. Marys Formation. The micro-coprolites represent the coprulid ichnospecies Coprulus oblongus. The fecal pellets are found in small clusters or strings of dozens to masses of many hundreds. Pellets range in size from approximately 0.4 – 2.0 mm wide by 1.0 – 5.0 mm long, and range in color from gray to brownish black. Their length/diameter ratio is always very nearly 2. These coprulids have been found in a variety of Miocene fossils/concretions including a uranoscopid neurocranium, naticid gastropod, bivalve shells, barnacle tests, and in pellet-backfilled sinuous burrows through sediment. Because the fecal pellets are often found in tiny spaces or spaces thought to be inaccessible to shelled invertebrates, the coprulids are attributed to small and soft-bodied polychaetes or other annelids. Some coprolites attributed to crocodilians from the lower-middle Miocene Calvert Formation were tunneled into, presumably the result of coprophagy, by some unknown kind of organism(s). These compound trace fossils are in the form of burrows that excavate the coprolites, the sides of which are sculptured by scratch/gouge marks.